2018
DOI: 10.1155/2018/1351964
|View full text |Cite
|
Sign up to set email alerts
|

Topological Characterization of Human and Mouse m5C Epitranscriptome Revealed by Bisulfite Sequencing

Abstract: Background Compared with the well-studied 5-methylcytosine (m5C) in DNA, the role and topology of epitranscriptome m5C remain insufficiently characterized. Results Through analyzing transcriptome-wide m5C distribution in human and mouse, we show that the m5C modification is significantly enriched at 5′ untranslated regions (5′UTRs) of mRNA in human and mouse. With a comparative analysis of the mRNA and DNA methylome, we demonstrate that, like DNA methylation, transcriptome m5C methylation exhibits a strong clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/ mouse [9,37,[45][46][47][48][49][50][56][57][58][59], zebrafish [51], plant [60][61][62], archaeal [63], and even viral [64,65] origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in [66]. Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/ mouse [9,37,[45][46][47][48][49][50][56][57][58][59], zebrafish [51], plant [60][61][62], archaeal [63], and even viral [64,65] origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in [66]. Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/mouse (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Blanco et al 2016;Amort et al 2017;Legrand et al 2017;Yang et al 2017;Wei et al 2018;Chen et al 2019;Huang et al 2019;Sun et al 2019), zebrafish (Yang et al 2019b), plant (Cui et al 2017;David et al 2017;Yang et al 2019a), archaeal (Edelheit et al 2013) and even viral (Courtney et al 2019a;Courtney et al 2019b) origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in (Trixl and Lusser 2019). Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis and serological examination have shown [43] that SRV-8 is more closely related to SRV-4, which can cause a lethal hemorrhagic syndrome when transmitted to Japanese macaques [57]. We have previously reported evidence showing that the expression of SRV proviral long terminal repeat (LTR) inside Jurkat cells and viral genome copies that are released into the culture medium gradually increased from two days to 10 days post-infection and tended to stabilize thereafter [47]. The productive infection of Jurkat cells with SRV-8 resembles SRV-1 infection of other human T cell lines, where the envelope gp20 protein is readily expressed after 10 days infection [45].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagosome formation was quantified in uninfected and SRV-8-infected Jurkat cells by detecting the endogenous LC3 protein, a specific hallmark of autophagosomes, to investigate whether and how the autophagic pathway in Jurkat cells is affected by infection with SRV-8 [48]. Using an immunofluorescent assay, the SRV-8-infected Jurkat cells had an increased number of LC3 puncta on day 10 post-infection relative to uninfected cells (Figure 1a,b), when the viruses were active in replication [47]. This finding suggests that SRV-8 infection increased the accumulation of autophagosomes in Jurkat cells.…”
Section: Srv-8 Infection Enhances Autophagosome Formation and Autophamentioning
confidence: 99%
See 1 more Smart Citation